Improved production of the recombinant phospholipase A1 from Polybia paulista wasp venom expressed in bacterial cells for use in routine diagnostics - Perez-Riverol, Amilcar [UNESP] (2020)
Phospholipase A1 (PLA1) is one of the three major allergens identified in the venom of P. paulista (Hymenoptera: Vespidae), a clinically relevant wasp from southeastern Brazil. The recombinant form of this allergen (rPoly p 1) could be used for the development of molecular diagnostic of venom allergy. Early attempts to produce rPoly p 1 using Escherichia coli BL21 (DE3) cells rendered high yields of the insoluble rPoly p 1 but with low levels of solubilized protein recovery (12%). Here, we aimed to improve the production of rPoly p 1 in E. coli by testing different conditions of expression, solubilization of the inclusion bodies and protein purification. The results showed that the expression at 16 °C and 0.1 mM of IPTG increased the production of rPoly p 1, still in the insoluble form, but with high solubilized protein yields after incubation with citrate–phosphate buffer with 0.15 M NaCl, 6 M urea, pH 2.6 at 25 ºC for 2 h. The venom allergen was also cloned in pPICZαA vector for soluble expression as a secreted protein in Pichia pastoris X-33 cells, rendering almost undetectable levels (nanograms) in the culture supernatant. In contrast, a sevenfold increase of the solubilized and purified rPoly p 1 yields (1.5 g/L of fermentation broth) was obtained after improved production in E. coli. The identity of the protein was confirmed with an anti-His antibody and MS spectra. Allergen-specific IgE (sIgE)-mediated recognition was evaluated in immunoblotting with sera of allergic patients (n = 40). Moreover, rPoly p 1 showed high levels of diagnostic sensitivity (95%). The optimized strategy for rPoly p 1 production described here, will provide the amounts of allergen necessary for the subsequent protein refolding, immunological characterization steps, and ultimately, to the development of molecular diagnostic for P. paulista venom allergy.